Pengaruh Persepsi Kemudahan, Persepsi Kegunaan, dan Persepsi Kepercayaan terhadap Niat Menggunakan Mobile Banking: Kasus Penggunaan Aplikasi BCA Mobile di Kota Bandung - Ghassani, Avisa; Raharso, Sri; Tiorida, Ermina (VISA: Journal of Vision and Ideas, 2024)
BCA Mobile is one of the mobile banking applications involved in competition among four major banks in Indonesia. However, currently, the BCA Mobile application is experiencing slower growth compared to its competitors in terms of user numbers, transaction volume, and value. To enhance user intention to use the mobile banking application, ease of use and usefulness are crucial factors. The Technology Acceptance Model (TAM) approach is used to examine the influence of perceived ease of use and perceived usefulness on the intention to use the technology. Additionally, the phenomenon of phishing in the financial sector in Bandung City and the doubts among some users in Bandung about the security of the BCA Mobile application are also concerns addressed. Therefore, the perception of trust in security is also included in this study. This research employs a quantitative descriptive method, involving a population of 447,968 with a sample of 402 respondents selected through non-probability and purposive sampling. Primary data was collected through a five-point Likert scale questionnaire and analyzed using tests for validity, reliability, descriptive statistics, classical assumptions, correlation, multiple linear regression, coefficient of determination, and hypothesis testing. The research findings indicate that the instruments used are valid and reliable. On average, users of the BCA Mobile application in Bandung find the application easy to use, useful, and trust its security, with average response values >4.30. The study also found a strong correlation between the independent and dependent variables, demonstrating a positive and significant influence of perceived ease of use, usefulness, and trust on the intention to use the BCA Mobile application by 32.2%. The remaining 67.8% is influenced by factors outside the scope of this study's model.